Artificial Intelligence, Religion, and Community Concern. - Rossano, Matt J. (Zygon: Journal of Religion & Science, 2001)
Future developments in artificial intelligence (AI) will likely allow for a greater degree of human-machine convergence, with machines becoming more humanlike and intelligent machinery becoming more integrated into human brain function. This will pose many ethical challenges, and the necessity for a moral framework for evaluating these challenges will grow. This paper argues that community concern constitutes a central factor in both the evolution of religion and the human brain, and as such it should be used as the organizing principle for moral evaluations of AI technologies.